2018
DOI: 10.1007/s10661-018-6816-y
|View full text |Cite
|
Sign up to set email alerts
|

The health hazards of potentially toxic metals in the daily diets of adults and children from a mining and smelting region (Hezhang County) in southwestern China

Abstract: Toxic metals accumulated in the human body are predominantly absorbed by the digestive tract in non-occupationally exposed populations. In the current study, we collected plowed soil samples, and investigated the varied food compositions in a mining and smelting area in southwestern China, to measure the concentrations of ten potentially toxic metals-As, Ba, Cd, Cr, Cu, Mn, Ni, Pb, Sr, and Zn. We collected information on the daily intakes of these metals to assess the health risks associated with their exposur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…This is the first time that greater shifts in male microbiome have been demonstrated, and there is unconformity with previous views based on the physical characteristics of women 44 . The lower metal burdens of women living in the contaminated site were proven in the authors' previous study 31 ; this could be the most important reason for the variation of the bacteria in the intestinal tract. The Different living habits (smoking and drinking) and work categories (farming and smelting) between men and females may contribute to this difference.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…This is the first time that greater shifts in male microbiome have been demonstrated, and there is unconformity with previous views based on the physical characteristics of women 44 . The lower metal burdens of women living in the contaminated site were proven in the authors' previous study 31 ; this could be the most important reason for the variation of the bacteria in the intestinal tract. The Different living habits (smoking and drinking) and work categories (farming and smelting) between men and females may contribute to this difference.…”
Section: Discussionmentioning
confidence: 65%
“…Because production and marketing principally occur locally, contaminated crops, vegetables, and animal foodstuff cause mineral metal accumulations in the bodies of local residents within the region 29,30 . In a previous study by the authors, exposure levels and the harmful health effects of multiple metals in local subjects were reported 31 . However, the effect of multiple metals on the human microbiome is still unclear.…”
mentioning
confidence: 99%
“…Lead compounds such as Pb oxide, carbonate, sulfate, and sulfide have been identified as the primary Pb species in soil collected near a Pb smelter no longer in operation where Pb levels ranged from 1100 to 5300 mg/kg ( Scheckel and Ryan, 2004 ). Environmental Pb contamination can cause serious long-term health effects, especially in children who are primarily at risk of Pb exposure through soil and dust contact ( Lanphear et al, 1998 ; Ryan et al, 2004 ; Schmitt et al, 1979 ; Shao et al, 2018 ; Thornton et al, 1990 ). The integrated exposure uptake biokinetic model (IEUBK; Hogan et al, 1998 , Laidlaw et al, 2017 ; USEPA, 1994 ) and more recent Stochastic Human Exposure and Dose Simulation (SHEDS) Multimedia IEUBK model characterize the major role of these Pb exposure routes ( Zartarian et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, anthropogenic activities, especially over the past few decades, have been documented as the key contributor to increased concentrations of heavy metals in soil and water. Chemical industries, tanneries, mining and smelting, iron and steel industries, agriculture, waste disposal, battery recycling and oil refining have been responsible for emissions of heavy metals to various environmental compartments [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have revealed that 90% of heavy metal intake in the human body is attributed to the consumption of plants [4,17]. Excessive exposure and accumulation of heavy metals in the body can result in acute and chronic health problems including cardiovascular disease, bone damage, kidney dysfunction, cancer as well as gastrointestinal, muscular, reproductive, neurological and genetic damages [1,6,18].…”
Section: Introductionmentioning
confidence: 99%